Prognostic Factors of Small Non-Functional Pancreatic Neuroendocrine Tumors and the Risk of Lymph Node Metastasis: A Population-Level Study - Tan, Qingquan; Wang, Xing; Li, Yichen; Liu, Yingyi; Liu, Xubao; Ke, Nengwen (Frontiers in Endocrinology, 2022)
Background: Small NF-PNETs are a heterogeneous subset of tumors with controversy regarding their optimal management. We aimed to analyze the prognostic factors of patients with small non-functional neuroendocrine tumors (NF-PNETs) and create a risk score for lymph node metastasis (LNM). Methods: Data of 751 patients with NF-PNETs ≤ 2 cm were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. Multivariate survival analysis was performed to analyze the prognostic factors. Logistic regression was used to identify risk factors for LNM Results: Of the 751 patients, 99 (13.2%) were confirmed to have LNM. In multivariate survival analysis, LNM (hazard ratio [HR], 2.12; 95% confidence interval [CI], 1.04-4.32, P = 0.040) was independently associated with disease-specific survival. Logistic regression identified tumor location in head of pancreas (odd ratio [OR], 4.33; 95%CI, 2.75-6.81; P < 0.001), size ≥ 1.5-2 cm (OR, 1.84; 95%CI, 1.17-2.87; P = 0.009) and grade III-IV (OR, 7.90; 95%CI, 1.79-34.90; P = 0.006) as independent risk factors of LNM. According to the OR value, the risk of LNM was scored as follows: a score of 1 for tumors located in body/tail of pancreas and 4 for those located in head; a score of 1 for tumors < 1 cm and 2 for those ≥ 1.5-2 cm; a score of 1 for tumors with grade I-II and 8 for those with grade III-IV. Finally, the median score for this cohort was 4, with an interquartile range of 3-6. Therefore, patients were classified as three groups based on the risk score system: a total score of 1-3 for low-risk, 4-6 for intermediate-risk (OR, 2.98; 95%CI, 1.59-5.60; P = 0.001) and 7-14 for high-risk (OR, 8.94; 95%CI, 4.50-17.7; P < 0.001), with an incidence of LNM 5.0%, 13.5% and 31.8% in each group (P < 0.001). Conclusion: Surgical resection with regional lymphadenectomy is recommended for small NF-PNETs with malignant potential of LNM. A risk score for LNM based on tumor grade, location and size may preoperatively predict LNM of small NF-PNETs and guide clinical practice.